2022
DOI: 10.3390/biom12091195
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine, an ROS Inhibitor, Alleviates the Pathophysiology of Hyperthyroidism-Induced Cardiomyopathy via the ROS/Ca2+ Pathway

Abstract: Hyperthyroidism is common and can induce cardiomyopathy, but there is no effective therapeutic strategy. The purpose of this study was to investigate the molecular mechanism of hyperthyroidism-induced cardiomyopathy (HTC) and the effect of N-acetylcysteine (NAC), an ROS inhibitor, on the pathophysiology of HTC in vivo and in vitro. Compared with those in the control groups in vivo and in vitro, TT3 and TT4 were significantly increased, the structure of myocardial cells was enlarged and disordered, and intersti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The Masson staining and Western-Blot results revealed that myocardial collagen synthesis was significantly increased in hyperthyroid rats, accompanied by impaired synthesis and clearance of extracellular matrix and obviously increased myocardial fibrosis. Similarly, Bao et al [29] reported a significant increase in interstitial fibrosis in cardiac myocytes of hyperthyroid rats, which is accompanied by weakened cardiac function and cardiac hypertrophy. In addition, Khamis et al [34] found significant upregulations of cardiac fibrosis-related genes of SMAD-2, SMAD-3, SMAD-4, TGF-β, and NF-κβ in myocardial tissues of hyperthyroid rats, and severely disturbed fibrotic changes in myocardial histopathology.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The Masson staining and Western-Blot results revealed that myocardial collagen synthesis was significantly increased in hyperthyroid rats, accompanied by impaired synthesis and clearance of extracellular matrix and obviously increased myocardial fibrosis. Similarly, Bao et al [29] reported a significant increase in interstitial fibrosis in cardiac myocytes of hyperthyroid rats, which is accompanied by weakened cardiac function and cardiac hypertrophy. In addition, Khamis et al [34] found significant upregulations of cardiac fibrosis-related genes of SMAD-2, SMAD-3, SMAD-4, TGF-β, and NF-κβ in myocardial tissues of hyperthyroid rats, and severely disturbed fibrotic changes in myocardial histopathology.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Bao et al . [ 29 ] reported a significant increase in interstitial fibrosis in cardiac myocytes of hyperthyroid rats, which is accompanied by weakened cardiac function and cardiac hypertrophy. In addition, Khamis et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact molecular mechanisms underlying this process remains unknown. It has been proposed that the intracellular ROS may disrupt in disrupt Ca 2 + homeostasis and inducing the cell apoptosis [26,27]. MCUb had been eluciated as a key regulator, exerting structural and physiological inhibitory of mitochondrial calcium exchange [28].…”
Section: Dicussionmentioning
confidence: 99%